δ Sct pulsation in magnetic Ap stars: The discovery of δ Sct pulsations in HD 218994AB and measurement of the magnetic fields of HD 218994A and HD 21190 - Kurtz, D. W. (2008)
We have discovered that at least one component of the visual binary star HD 218994AB is a δ Sct star. The primary star of this system is a known rapidly oscillating Ap (roAp) star; therefore, it is possible that it is both an roAp star and a δ Sct star - a hybrid. There are no confirmed such hybrid roAp-δ Sct stars, and they are predicted theoretically not to exist. More probably, HD 218994B is the δ Sct star, as it is 0.54 mag fainter than the primary and also lies in the δ Sct instability strip. It then offers the potential to determine Teff and L for the primary which appears to be one of the more evolved roAp stars and an important test the theoretically calculated roAp star instability strip. In this case, the system also is important since the stars are a co-eval pair of very similar mass, yet one is a magnetic roAp star and the other is probably a non-magnetic δ Sct star with a normal spectrum. We detect a significant longitudinal magnetic field strength of 440 ± 23 G in the roAp star HD 218994A. We also present the first measurement of the longitudinal magnetic field strength for the δ Sct star HD 21190, the most-evolved Ap star known. We obtain a formally significant value of 47 ± 13 G. If confirmed, this will make HD 21190 the first magnetic δ Sct star known.